A Flexible and Efficient Key Distribution Scheme for Renewable Wireless Sensor Networks. (31st May 2009) - Shen, An-Ni; Guo, Song; Leung, Victor
Abstract : Many applications of wireless sensor network require secure data communications, especially in a hostile environment. In order to protect the sensitive data and the sensor readings, secret keys should be used to encrypt the exchanged messages between communicating nodes. Traditional asymmetric key cryptosystems are infeasible in WSN due to its low capacity at each senor node. In this paper, we propose a new key distribution scheme for hierarchical WSNs with renewable network devices. Compared to some of the existing schemes, our key establishment methods possess the following features that are particularly beneficial to the resource-constrained large-scale WSNs: (1) robustness to the node capture attack, (2) flexibility for adding new network devices, (3) scalability in terms of storage cost, and (4) low communication overhead.